2015
DOI: 10.3390/resources4040831
|View full text |Cite
|
Sign up to set email alerts
|

Key Challenges and Opportunities for Conjunctive Management of Surface and Groundwater in Mega-Irrigation Systems: Lower Indus, Pakistan

Abstract: This paper focuses on the scope of conjunctive management in the Lower Indus part of the Indus Basin Irrigation System (IBIS), and the contribution this could make towards food security and socioeconomic development. The total Gross Command Area (GCA) of the Lower Indus is 5.92 Mha, with a cultivable command area (CCA) of 5.43 Mha, most of which is in Sindh Province. There is a limited use of groundwater in Sindh (about 4.3 Billion Cubic Meter (BCM)) for two reasons: first, there is a large area where groundwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 3 publications
0
25
0
Order By: Relevance
“…The central part is extended from north-east to south-west, dominated by the lower Indus plain, Indus piedmont plain and Indus deltaic plain [ 32 ]. The available groundwater resource in Sindh is about 5 million acre foot (MAF) and has ample potential for irrigation however, the use of groundwater is comparatively lesser (4.3 billion cubic meter) than surface water because of two primary reasons: firstly, most of the area is lying on saline or brackish water; secondly, canal command areas are being provided with surface irrigation supplies [ 33 ]. The river Indus, having an influent behavior, loses water to the underlying aquifer, as it lies on a slight ridge, which slopes away in a lateral direction up to Larkana District.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The central part is extended from north-east to south-west, dominated by the lower Indus plain, Indus piedmont plain and Indus deltaic plain [ 32 ]. The available groundwater resource in Sindh is about 5 million acre foot (MAF) and has ample potential for irrigation however, the use of groundwater is comparatively lesser (4.3 billion cubic meter) than surface water because of two primary reasons: firstly, most of the area is lying on saline or brackish water; secondly, canal command areas are being provided with surface irrigation supplies [ 33 ]. The river Indus, having an influent behavior, loses water to the underlying aquifer, as it lies on a slight ridge, which slopes away in a lateral direction up to Larkana District.…”
Section: Introductionmentioning
confidence: 99%
“…A part of the flow drains towards the desert in the east, whereas another flows towards the Khirthar Hills. During the harvest season of winter crops, the flow in the river below Sukkur Barrage becomes negligible, so the river starts receiving groundwater, especially from the left bank [ 33 ]. Studies have revealed contamination of groundwater by a variety of contaminants in Sindh province.…”
Section: Introductionmentioning
confidence: 99%
“…Declines in groundwater levels have been recorded across many parts of the Indus River basin in Pakistan, with irrigation expansion also leading to waterlogging and secondary salinization in shallow groundwater table areas (Qureshi, 2015). In Balochistan Province, groundwater levels are declining at a rate of 2-3 m yr¹, and in upland areas away from major command areas groundwater declines as high as 5 m yr¹ have been recorded (van Steenbergen et al, 2015). In India, out of the total 6881 assessment units (blocks/mandals/talukas/firkas), 1186 units in various states (17%) have been categorized as 'over-exploited', indicating groundwater extraction exceeding the annually replenishable groundwater recharge.…”
Section: Groundwater Systems and Their Utilization In South Asiamentioning
confidence: 99%
“…The article by van Steenbergen et al [4] presents a regional overview of water issues in the Lower Indus region of Pakistan. They describe the need for updated policies and conjunctive management of surface water and groundwater resources in an area with limited groundwater usage.…”
Section: Groundwater Quantity Management Legal Issues and Over Expmentioning
confidence: 99%
“…Five articles [4][5][6][7][8] examine various aspects of groundwater quantity by addressing groundwater management, legal issues, and over exploitation of groundwater.…”
Section: Groundwater Quantity Management Legal Issues and Over Expmentioning
confidence: 99%